PENGARUH FINANCIAL TECHNOLOGY, FINANCIAL LITERACY, DAN HEDONISM LIFESTYLE TERHADAP PENGELOLAAN KEUANGAN SISWA SMKN 4 SURABAYA - Priasiwi, Dhanis Ayu; Rochmawati, Rochmawati (Promosi: Jurnal Program Studi Pendidikan Ekonomi, 2023)
This research aims to determine the influence of financial technology, financialliteracy, and hedonism on the financial management of students at SMKN 4Surabaya. This type of research is ex-post facto research with research subjects,namely class XI students majoring in financial and institutional accounting atSMKN 4 Surabaya, totaling 102 students. The sampling technique used waspurposive sampling with a total of 64 students. The data analysis technique usesmultiple linear regression analysis with SPSS 25 software. The research resultsshow that (1) financial technology, financial literacy, and a hedonistic lifestylesimultaneously have a significant effect on students' financial management. (2)Financial technology has a positive and significant effect on students' financialmanagement. (3) Financial literacy has a positive and significant effect on students'financial management. (4) The hedonism lifestyle has a positive and significanteffect on students' financial management. The adjusted R square value in this studywas 50.5%, which means that the contribution of financial technology, financialliteracy, and a hedonism lifestyle to students' financial management was 50.5%,while the remaining 49.5% was influenced by other variables outside of thisresearch.